Evaluating the reliability of a microperimetry-based method for assessing visual function in the junctional zone of geographic atrophy lesions - A. Yasin Alibhai; Eric M. Moult; Muhammad Usman Jamil; Khadija Raza; Marco U. Morales; Ramiro Ribeiro; Caroline R. Baumal; James G. Fujimoto; Nadia K. Waheed (International Journal of Retina and Vitreous)
Abstract Purpose To assess the repeatability of a microperimetry methodology for quantifying visual function changes in the junctional zone of eyes with geographic atrophy (GA) in the clinical trial context. Methods A post hoc analysis of the OAKS phase III trial was conducted, which enrolled patients with GA secondary to age-related macular degeneration. Microperimetry using a standard 10 − 2 fovea centered grid was performed at baseline and follow-up visits. GA regions were traced on fundus autofluorescence (FAF) images. Two graders independently registered baseline microperimetry images with baseline FAF images in a sampling of 30 eyes from the OAKS study. Agreement between the two graders’ assessments of mean sensitivity and the number of scotomatous points within a ± 250 𝜇m GA junctional zone was assessed. Results The intraclass correlation (ICC) and coefficient of repeatability (CoR) for the mean junctional zone sensitivity were 0.987 and 0.214 dB, respectively. The ICC and CoR for the total number of scotomatous points within the junctional zone were 0.991 and 1.42, respectively. Conclusions The repeatability of the methodology and its compatibility with standard MP acquisitions appear to make it well-suited for identifying and analyzing retinal sensitivity within high-risk areas of the retina. Summary We present a microperimetry-based methodology for assessing visual function changes in the junctional zone of geographic atrophy lesions using a standard 10 − 2 fovea centered grid in a clinical trial context. The approach’s repeatability and compatibility with standard microperimetry grids may make it useful for assessing the effects of GA therapeutics.